HUBUNGAN KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PASIEN RAWAT INAP BPJS KESEHATAN - Tobing, Indridani Rogate; Ginting, Jesika Br; Ginting, Johannes Bastira; Dameria, Dameria (Jurnal Keperawatan Priority, 2023)
Indonesia is one of the countries that has created a social security program to improve public health under the Health Social Security Organizing Agency (BPJS). The hospital is part of a health care system that broadly provides health services, including medical services, medical support, medical rehabilitation, and care services through emergency, outpatient, and inpatient units. This study aims to determine and analyze the relationship between service quality factors and patient satisfaction. This quantitative research method uses a descriptive approach (cross-sectional survey) and associative analysis conducted at Royal Prima Medan Hospital in March 2022. The population is all inpatients of BPJS Health users, sampling using non-probability, accidental sampling type-univariate, bivariate (Chi-Square) data analysis with a significance level of 0.05. The results showed that the variables Tangibles (p-value=0.001), Reliability (p-value=0.004), Responsiveness (p-value = 0.007), Assurance (p-value = 0.000), Empathy (p-value = 0.003), had a significant relationship with patient satisfaction with a p-value ≤ 0.05. Conclusion Based on the results of research and discussion, it can be concluded that service quality (dimensions of tangibles, reliability, responsiveness, assurance, empathy) is related to the satisfaction of inpatients using BPJS Health at Royal Prima Medan Hospital.